DESAIN DAN UJI COBA MEDIA BERBASIS WEBLOG PADA MATERI PERKEMBANGAN MODEL ATOM TERINTEGRASI NILAI-NILAI ISLAM - Elvi Yenti; Marsya Diah Lestari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research was instigated with the education aiming as a communication process form students who believe, and have noble character and have good knowledge. In order to unite scientific knowledge and Islamic values, so innovation that can make these two sciences into one unified whole is needed. This research aimed at producing Weblog based learning media design and finding out the appropriateness level and student response to the media. It was Research and Development with Design Development Research (DDR) model. The result of this research was Weblog learning media on Islamic Values integrated the Development of the Atomic Model lesson. a) the validity level consisted of the percentages 92.5% by media expert validators with very valid criterion, 100% by material expert validators with very valid criterion, and 84.37% by integration expert validators with very valid criterion; b) Chemistry subject teacher response through practicality test showed that the percentage was 95% with very practical criterion; and c) the response of the tenth-grade students of class to the media showed that the percentage was 85% with very good criterion.